Development of Guided Inquiry LKPD Based on Creativity on The Concept of Air Pollution - Pratama, Zidan Rachmat; Setiono; Suhendar; Nuranti, Gina (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2025)
Background: This study aims to develop a guided inquiry-based Student Worksheet (LKPD) oriented towards enhancing creativity, to connect the concept of air pollution with real-world phenomena. It also seeks to describe the attractiveness, ease of use, usefulness, and effectiveness of the LKPD in the learning process Methods: The research employed is a development method, commonly referred to as Research and Development (R&D). The study involved material experts and media experts to validate the LKPD, as well as a science teacher and 35 seventh-grade students from SMP Islam Nurul Huda Cicantayan. The instruments used included student response questionnaires, as well as pretest and posttest questions. Results: The validation results from the material expert, which assessed content feasibility and accuracy, showed a score of 71% and were categorized as valid. Meanwhile, validation by the media expert resulted in a score of 66%, also categorized as valid, indicating that the product is suitable for use by students as it aids the learning process. The N-gain score obtained was 0.8, which falls in the high category (g ≥ 0.7), indicating that the LKPD is effective. Additionally, student response questionnaires showed a score of 76%, categorized as interesting/practical. The R&D study proved effective, as shown by the trial results where students became more active and better understood the concept, particularly in the topic of air pollution. Conclusion: Based on the results, the developed Student Worksheet (LKPD) is considered valid and effective for use in the learning process.